THE STUDY FOCUSES ON THE LEVEL OF PARTICIPATION OF THE PENTAHELIX MODEL IN THE DEVELOPMENT OF MICRO-ENTERPRISES OF MUSLIM WOMEN IN THE CITY OF KEDIRI - Saadah, Nur Lailis; Ulum, Syahrul; Q, Sahal Awaludin; Siddiq, Harun Ash (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to determine the level of participation of the pentahelix model in the development of Muslim women's microbusinesses in Kediri City as well as the factors behind the pentahelix actors in the development of microbusinesses in Kediri City. The research method used in this research is a combination method, namely quantitative and qualitative research methods carried out sequentially (sequential explanatory). Researchers used a sample of 97 Muslim women as respondents who met the specified criteria. The research instruments were questionnaires and interviews as data collection tools. The results of the data analysis based on the Likert scale value index show that the levels of pentahelix participation are sequentially: community (79%, government and media (73%, academics (66% and business/private 65%. Meanwhile, based on the T test via SPSS version 25, it is known that there is an influence between Pentahelix (X) participation and Micro Business Development (Y) in Kediri City. Judging from the Sig value of 0.00, which means it is smaller than the probability of 0.05, Ho is rejected and Hi is accepted. looking at the determinant value of a variable This quantitative data is supported by the results of interviews with several respondents, who stated that the factors that influence community pentahelix actors have high scores. The factors that influence business, private, and academic actors that have the lowest scores compared to other pentahelix actors are internal and external factors, which are reviewed in depth in qualitative research.